2017
DOI: 10.3201/eid2305.161788
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Analysis ofBacillus cereusIsolated after Death of Preterm Neonates, Nice, France, 2013

Abstract: After the deaths of 2 preterm neonates with Bacillus cereus systemic infection in the same intensive care unit, we investigated the pathogenic potential of this bacterium. Genetic and virulence analysis indicated the neonates were infected with 2 different strains with a virulence potential similar to environmental strains, indicating likely patient immune response failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…The underlying condition of the last one was unknown. Consistent with previous findings [ 14 , 18 ], our study confirms that the majority of patients were premature newborns, followed by elderly people. It is suspected that B .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The underlying condition of the last one was unknown. Consistent with previous findings [ 14 , 18 ], our study confirms that the majority of patients were premature newborns, followed by elderly people. It is suspected that B .…”
Section: Discussionsupporting
confidence: 93%
“…cereus induces local and systemic infections [ 5 13 ]. The main described conditions are septicemia, endophthalmitis, pneumonia, endocarditis, meningititis and encephalitis, especially in immunosuppressed individuals such as neonates, resulting in the patient death in about 10% of cases [ 9 , 14 19 ]. In addition, several cases of fulminant infections similar to anthrax, and affecting healthy persons, have also been reported [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Refrigeration or freezing of pasteurized DHM should be strictly applied to control the growth of any remaining microorganism. Although a relative high number of B. cereus cells has been usually found in foodborne outbreaks, lower stomach acidity in preterms may allow a higher survival of cells (Stenfors Arnesen et al, 2008 ; Lotte et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several bacteria are considered unacceptable because they are usually pathogenic, such as Gram negative bacilli, including Pseudomonas aeruginosa , E. coli , Kliebsiella , Enterobacter , Serratia , Salmonella and Proteus , Group B streptococcus , and Staphylococcus aureus . Bacillus cereus is an environmental pathogen that is found in neonatal units and has been associated with severe sepsis in preterm infants . However, these studies did not find any reported cases of B. cereus infection related to human milk.…”
Section: Resultsmentioning
confidence: 99%